The attractiveness of university and corporate anchor tenants in the conception of a new cluster. Issue 8 (3rd August 2021) - Dimos, Christos; Fai, Felicia M.; Tomlinson, Philip R.
ABSTRACT: Using an ex-ante, policymaker perspective, this study focuses upon a proposal for a new university (automotive) research institute (URI) – the University of Bath's Institute for Advanced Automotive Propulsion Systems (IAAPS) – and its role in the conception of a new industrial cluster. Analysing unique survey data, we identify the key characteristics of the firms most likely to observe future potential benefits from the presence of this proposed public anchor (1) in isolation and (2) when the proposed public anchor is established with a research-based relationship with a co-located private anchor. We find the presence of a private anchor amplifies the attractiveness of the public anchor, heightening the likelihood of a cluster emerging. We discuss implications for policy.